What is Racism? Othering, Prejudice and Hate-motivated Violence - Tony Jefferson (International Journal for Crime, Justice and Social Democracy, 2015)
The paper’s concern is the current difficulty, in journalism, the academy and politics, of discussing questions to do with race, ethnicity, difference and immigration because of the fear of being called a racist. It starts with an analysis of biographical interview data drawn from fifteen people who had variously acquired the label racist and who were part of a small-scale study into racism in the Midlands city of Stoke-on-Trent, UK conducted between 2003 and 2005. The interviews used the free association narrative interview method. This analysis revealed that most people do not consider themselves racist and that having a conviction for a racially aggravated offence or being a member of a far right organisation was not able to differentiate racists from non-racists. It also revealed a spectrum of attitudes towards immigrants or particular ethnic groups: strong expressions of hatred at one end of the spectrum; strong prejudicial feelings in the middle; and a feeling that ‘outsider’ groups should not benefit at the expense of ‘insiders’ (called ‘othering’) at the other end. The turn to theory for assistance revealed that, although hatred, prejudice and ‘othering’ are not the same thing, and do not have the same origins, they have become elided. This is primarily because cognitive psychology’s hostility to psychoanalysis marginalised hatred whilst its exclusive preoccupation with prejudice came effectively to define racism at the individual level. Progress in thinking about racism might consist of abolishing the term and returning to thinking about hatred, prejudice and ‘othering’ separately.